Tissue reaction and integration of polyamide and acrylonitrile-butadiene-styrene spheres in rat subcutaneous tissue - Junior, Deusdete Conceição Gomes; Nassar, Eduardo José; Neto, Francisco de Assis Dórea; Lima, Alessandra Estrela; Honsho, Cristiane dos Santos; Filho, Emanoel Ferreira Martins; Oriá, Arianne Pontes (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Gomes Junior D.C., Nassar E.J., Dórea Neto F.A., Estrela-Lima A, Honsho C. dos S., Martins Filho E. & Oriá A.P. Tissue reaction and integration of polyamide and acrylonitrile-butadiene-styrene spheres in rat subcutaneous tissue. [Reação e integração tecidual de esferas de acrilonitrila butadieno estireno e poliamida em subcutâneo de ratos.] Revista Brasileira de Medicina Veterinária, 38(Supl.1):93-98, 2016. Programa de Pós-Graduação em Ciência Animal nos Trópicos, Universidade Federal da Bahia, Av. Ademar de Barros, 500, Ondina, Salvador, BA 40170-110, Brasil. E-mail: arianneoria@ufba.br We investigated the infiltration and tissue reaction of polyamide and acrylonitrile-butadiene-styrene (ABS) spheres prepared by rapid prototyping. Accordingly, three groups of six Wistar rats each were formed; G1, where animals received ABS implants; G2, where animals received polyamide implants and the control group where the animals received polymethylmethacrylate implants. Implants were inserted subcutaneously in the dorsal thoracic region and the animals were euthanized 60 days after implant insertion to evaluate tissue reaction and incorporation. The spheres were sectioned for macroscopic evaluation of tissue infiltration, and capsule fragments were collected for histopathologic evaluation. In macroscopic evaluation, all samples showed the presence of a thin tissue capsule that was strongly adhered to the implants in G1, moderately adhered to the implants in G2 and discretely adhered to the control group. The collected fragments of G1 and G2 had a similar appearance on histopathologic examination, however the inflammatory reaction observed in the animals of G1 was more discreet. Evidence of infection or foreign body reaction was not observed in any of the fragments, and all groups showed a mild mononuclear inflammatory reaction. Macroscopically, tissue infiltration was observed in G1 and G2. The results showed that the implants were well tolerated and allowed tissue integration.